2020
DOI: 10.3390/jmse8070490
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution for Estimating Bearing Capacity of a Closed Soil Plug: Verification Using An On-Site Static Pile Test

Abstract: When the open-ended pile penetrates the soil layer, the resistance generated by the soil plug cannot be ignored. A pile with a full-size pressure sensor installed at pile tip can detect resistance more accurately than a microsensor when the pile penetrates into the soil. In this paper, the pile installed full-size pressure sensor was used for penetration test and the relationship between formation parameters and pile tip force is obtained. Using the solution of the Kelvin problem in infinite space and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As a result, researchers have conducted extensive research on the topic of the soil squeezing effect of static piles from many perspectives. The topic is now being studied through the use of theoretical calculation approaches [11][12][13][14][15][16][17], laboratory and field experiments [3,4,[18][19][20][21] and numerical calculations [22][23][24][25][26][27]. Among them, three main theories may be used to evaluate the mechanical properties of static piles: the cavity expansion method (CEM) [11][12][13][14], the strain path method (SPM) [5,7,16] and the limit equilibrium method (LEM) [17], although each has its own set of limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, researchers have conducted extensive research on the topic of the soil squeezing effect of static piles from many perspectives. The topic is now being studied through the use of theoretical calculation approaches [11][12][13][14][15][16][17], laboratory and field experiments [3,4,[18][19][20][21] and numerical calculations [22][23][24][25][26][27]. Among them, three main theories may be used to evaluate the mechanical properties of static piles: the cavity expansion method (CEM) [11][12][13][14], the strain path method (SPM) [5,7,16] and the limit equilibrium method (LEM) [17], although each has its own set of limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The topic is now being studied through the use of theoretical calculation approaches [11][12][13][14][15][16][17], laboratory and field experiments [3,4,[18][19][20][21] and numerical calculations [22][23][24][25][26][27]. Among them, three main theories may be used to evaluate the mechanical properties of static piles: the cavity expansion method (CEM) [11][12][13][14], the strain path method (SPM) [5,7,16] and the limit equilibrium method (LEM) [17], although each has its own set of limitations. In addition, Liu [19] conducted piling tests under various conditions of centrifugal acceleration and discovered that the displacement of soil increased as piling depth increased.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of offshore monopiles from driving to using are different from those of onshore small-size piles, and their time effect also shows great differences [3]. Existing research results [4][5][6][7][8] are difficult to meet the needs of engineering practice. In particular, the design basis for monopile bearing capacity in API and DNV specifications [9,10] are derived from the test data of small-diameter pile foundation [11,12], and the size effect significantly affects the bearing capacity of pile foundation [13], which is not well applicable to large-diameter monopiles.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] combined the consequence with the result from a model-socketed pile test on reef lime stone and obtained the variation law of the bearing capacity with the pile tip displacement. Su et al [6] conducted a numerical analysis on the effect of soil plugging and compared it with field measurements, and they found that the ultimate bearing capacity of the soil plug had a linear relationship with the soil parameters Standard Penetration Test(SPT) and CPT. In fact, prefabricated hollow pipe piles have become the most used due to their higher cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%